2017
DOI: 10.1186/s40813-017-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of vaccines to control pathogen spread in pig populations

Abstract: Vaccine efficacy has often been studied from the viewpoint of individual direct clinical protection. For several vaccines, a decrease in pathogen shedding in vaccinated animals has also been documented, which suggests that transmission between individuals has the potential to be reduced. In addition, vaccination induces an immune response in the host potentially decreasing susceptibility to infection in comparison with immunologically naïve animals. As a collective result of individual vaccinations, vaccine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…As such the burden of keeping current with IAV-S vaccine research is borne by practicing veterinarians. Multiple IAV-S vaccines are licenced for use in swine, including autogenous vaccines (custom produced to match farm viral isolates), but messaging on vaccination programs vary and lacks consensus with respect to differing vaccine, target population, and herd management characteristics [ 15 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such the burden of keeping current with IAV-S vaccine research is borne by practicing veterinarians. Multiple IAV-S vaccines are licenced for use in swine, including autogenous vaccines (custom produced to match farm viral isolates), but messaging on vaccination programs vary and lacks consensus with respect to differing vaccine, target population, and herd management characteristics [ 15 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies to address the interaction between MHCs and epitopes have been limited for nonhuman species such as pigs. The development of disease resistance and effective vaccines against major infectious diseases in pigs is a critical issue in large-scale pig farming as diseases cause significant losses in productivity [ 23 , 24 ]. However, interactions between swine leukocyte antigens (SLAs) and the epitopes of viral pathogens have not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the FMD vaccine was injected in the neck, while the [23] and three types of hypothetical farm size are assumed: farms with 100, 500, and 1,000 sows. 2) Only negligible amounts of electricity and labor are required to maintain and operate the heating equipment for foot-and-mouth disease vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…Cho et al (2020) Asian-Australas J Anim Sci 33:634-639 vaccination site was the ham in the previous study [11]. Ko et al [2] found that the incident rate of lesions differed with different sites of injection, and it was higher in the neck than in pork ham.…”
mentioning
confidence: 91%
See 1 more Smart Citation